Long-Term Results of Mitral Valve Repair - Francisco Diniz Affonso da Costa; Daniele de Fátima Fornazari Colatusso; Gustavo Luis do Santos Martin; Kallyne Carolina Silva Parra; Mariana Cozer Botta; Eduardo Mendel Balbi Filho; Myrian Veloso; Gabriela Miotto; Andreia Dumsch de Aragon Ferreira; Claudinei Colatusso (Brazilian Journal of Cardiovascular Surgery)
Abstract Introduction: Current guidelines state that patients with severe mitral regurgitation should be treated in reference centers with a high reparability rate, low mortality rate, and durable results. Objective: To analyze our global experience with the treatment of organic mitral regurgitation from various etiologies operated in a single center. Methods: We evaluated all surgically treated patients with organic mitral regurgitation from 2004-2017. Patients were evaluated clinically and by echocardiography every year. We determined early and late survival rates, valve related events and freedom from recurrent mitral regurgitation and tricuspid regurgitation. Valve failure was defined as any mitral regurgitation ≥ moderate degree or the need for reoperation for any reason. Results: Out of 133 patients with organic mitral regurgitation, 125 (93.9%) were submitted to valve repair. Mean age was 57±15 years and 52 patients were males. The most common etiologies were degenerative disease (73 patients) and rheumatic disease (34 patients). Early mortality was 2.4% and late survival was 84.3% at 10 years, which are similar to the age- and gender-matched general population. Only two patients developed severe mitral regurgitation, and both were reoperated (95.6% at 10 years). Freedom from mitral valve failure was 84.5% at 10 years, with no difference between degenerative and rheumatic valves. Overall, late ≥ moderate tricuspid regurgitation was present in 34% of the patients, being more common in the rheumatic ones. The use of tricuspid annuloplasty abolished this complication. Conclusion: We have demonstrated that mitral regurgitation due to organic mitral valve disease from various etiologies can be surgically treated with a high repair rate, low early mortality and long-term survival that are comparable to the matched general population. Concomitant treatment of atrial fibrillation and tricuspid valve may be important adjuncts to optimize long-term results.